2021
DOI: 10.1053/j.jvca.2021.02.008
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Pneumothorax/Pneumomediastinum in Mechanically Ventilated COVID-19 Patients

Abstract: Objective To determine the incidence, predictors, and outcome of pneumothorax (PNX)/pneumomediastinum (PMD) in coronavirus disease 2019 (COVID-19) acute respiratory distress syndrome (ARDS). Design Observational study. Setting Tertiary-care university hospital. Participants One hundred sixteen consecutive critically ill, invasively ventilated patients with COVID-19 ARDS. Interventions Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

10
113
5
10

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 88 publications
(138 citation statements)
references
References 49 publications
10
113
5
10
Order By: Relevance
“…26,27 Belletti et al evaluated predictors of PNX/PMD in mechanically ventilated COVID-19 patients and concluded that delayed intubation was an independent predictor of PNX/PMD development. 28 In that study, the group who developed PBT had a longer time from symptoms onset to intubation than the group who did not develop PBT (13 vs 10 days, p=0.004). This higher incidence of PBT in NIPPV, as well as the reported cases of spontaneous PNX, may support that the underlying cause of PNX/PMD is due to an underlying virus-induced mechanism as part of the natural course/sequela of the SARS-CoV -2 disease rather than a mechanical PPV-induced complication caused by high transpulmonary pressure.…”
mentioning
confidence: 79%
See 2 more Smart Citations
“…26,27 Belletti et al evaluated predictors of PNX/PMD in mechanically ventilated COVID-19 patients and concluded that delayed intubation was an independent predictor of PNX/PMD development. 28 In that study, the group who developed PBT had a longer time from symptoms onset to intubation than the group who did not develop PBT (13 vs 10 days, p=0.004). This higher incidence of PBT in NIPPV, as well as the reported cases of spontaneous PNX, may support that the underlying cause of PNX/PMD is due to an underlying virus-induced mechanism as part of the natural course/sequela of the SARS-CoV -2 disease rather than a mechanical PPV-induced complication caused by high transpulmonary pressure.…”
mentioning
confidence: 79%
“…45,46 In a study by Capaccione et al, the time from intubation to PNX event was 14.9 days which is similar to that described by Belletti et al, in which the time from intubation to PNX was 14 days. 15,28 Most patients who developed PBT in our study died (88%). The occurrence of PBT did not change the overall outcome of our study population.…”
mentioning
confidence: 81%
See 1 more Smart Citation
“…Pneumomediastinum (PMD) and pneumothorax (PNX) occur frequently in mechanically ventilated patients with coronavirus disease 2019 (COVID-19)-related acute respiratory distress syndrome (ARDS) [ 1 ], with a reported incidence up to 24% in the first Italian pandemic wave [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…Pneumothorax and pneumomediastinum are relatively common complications in patients with extensive alveolar damage requiring mechanical ventilation 1 . In lung areas exposed to high pressure during mechanical ventilation, alveolar rupture may develop and cause pneumothorax 2 .…”
mentioning
confidence: 99%